The Effect Of Progressive Muscle Relaxation Exercise And Diaphragmatic Breath On Quality Of Life In Diabetes Mellitus Patients - Sukma Wicaturatmashudi; Ismar Agustin; Prahardian Putri (CV. AFDIFAL MAJU BERKAH, 2022)
Diabetes Mellitus is a metabolic disease that has an impact on almost all organ systems of the body. The risk of complications and the long treatment period and even a lifetime is one of the triggers for the worsening quality of life. This study aims to determine the effect of a combination of progressive muscle relaxation exercises and diaphragmatic breathing exercises on the quality of life in Diabetes Mellitus patients at Siti Khadijah Islamic Hospital Palembang. The design of this study was a quasi-experimental pre post test with control group. The population in this study were all patients with diabetes mellitus at the Siti Khadijah Islamic Hospital in Palembang. Data analysis was performed with univariate and bivariate. Bivariate analysis using t test dependent and independent t test. The results showed that there was a significant difference in the mean quality of life before and after the treatment of progressive muscle relaxation exercise and diaphragmatic breathing exercise (p value = 0.014) and there was a significant effect of progressive muscle relaxation exercise and diaphragmatic breathing exercise on the quality of life value (p value = 0.005). Based on the results of the study, it is recommended to implement progressive muscle relaxation exercises and diaphragmatic breathing exercises in patients with Diabetes Mellitus on a regular and continuous basis.